Pengaruh Sosialisasi, Pengetahuan, Sanksi dan Kualitas Pelayanan Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor - Lucya Herty Apriliyani (Papanda Publisher, 2022)
This research aims to determine the effect of socialization, knowledge, sanctions and quality of service on compliance of motor vehicles taxpayers in the Office with SAMSAT Majalengka. The method used is by using descriptive and verificative analysis techniques. The sample in this research counted 100 respondents by using the incidental sampling method. Data collection techniques that is by distributing questionnaires. Testing instrument data is done validity and reliability tests. Test of classic assumptions and Multiple Regression Analysis with the help of SPSS 21 for windows program. Based on the results of the research show that partially socialization variables, knowledge and sanctions affect the taxpayer compliance. While the variable service quality does not effect taxpayers compliance.